Lung biology and lung disease - Torday, John S. (Henry Stewart Talks, 2007)
The evolution of the vertebrate lung, Vertebrate evolution from unicellular organisms is reflected in lung development, Stretch-regulated pathways of lung development leading to homeostasis can fail, leading to chronic lung disease, The cell/molecular pathways that integrate lung development and homeostasis can serve to effectively diagnose and treat chronic lung disease
Updated at 2011/07/07